Design and implementation of computer- and network-assisted system for selecting priorities in the Joint College Entrance Examinations. (4th August 2005) - Chou, Li-Der; Yen, Sung-Ming; Wu, Po-Ching; Chung, Chi-Hau; Hung, Kuo-Chih; Chen, Shang-Jie; Lai, Wei-Cheng
The traditional way of filling out the Joint College Entrance Examination (JCEE) priorities is done manually in Taiwan. Top 80 priorities are to be filled out on the priority card using 2B pencils. What happens is that it is easy to misfill the card with wrong priorities or the card could even be messed up such that the card reader cannot identify the answers. Thus, not only does the process become more complicated, but also mistakes could easily take place. It is becoming more and more popular for businesses to computerise many of their operations, such as the network tax reporting system, the online signing up for the recommendation of entering schools, etc., and replace the traditional complicated manual job. In this paper, we propose a method of computerised dispatch operation to replace the traditional half-computerised process for filling out the priorities in the entrance examination. More accuracy was achieved and the whole process became easier. In addition, it was convenient for all candidates.